2021
DOI: 10.3390/nu13082819
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Eating Disorders and Perception of Body in Young Adults Associated with Sex

Abstract: (1) Background: The integrated approach to the prevention and treatment of eating disorders (EDs) requires knowledge and can be used only when specific risk factors are known. The aim of this study was to examine the differences in food choices and eating behavior between males and females; (2) Methods: This study comprised 148 females and 27 males aged from 18 to 26-years-old (MEAN ± SD = 21.4 ± 1.86 years old). Information about EDs was obtained from four different measures: the body mass index (BMI), the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
3
1
1
Order By: Relevance
“…In this study, 484 participants (44.3%) achieved ESP instrument scores of 2 or higher. This rate is significantly higher than that reported in the USA by Fruehwirth et al (2023) (24%) but lower than that reported by Purkiewicz et al (2021) (69%) [79,80]. The variation in the results may be related to the fact that the current study encompassed a wider age range and included more participants.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, 484 participants (44.3%) achieved ESP instrument scores of 2 or higher. This rate is significantly higher than that reported in the USA by Fruehwirth et al (2023) (24%) but lower than that reported by Purkiewicz et al (2021) (69%) [79,80]. The variation in the results may be related to the fact that the current study encompassed a wider age range and included more participants.…”
Section: Discussioncontrasting
confidence: 69%
“…Numerous studies have already pointed out the importance of the use of new technologies in the appearance and maintenance of EDs [ 50 , 51 ]. On the other hand, exposure to the media seems to precede the emergence of eating disorders, since ideas, models, and innumerable products and services that do not reproduce common women or men, nor represent a healthy body weight are disseminated on TV [ 52 ]. In a longitudinal study carried out a few years ago, it was found that a longer time of exposure to television programs predicted the internalization of the ideals of appearance and thinness one year later [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our scale, we developed the dimension “health condition and eating habits”, which included two items: “Suffer from diarrhea, constipation and/or chronic gastric diseases” and “High study pressure, fast and irregular eating habits”. The unhealthy state of digestive system, eating disorders, and unhealthy eating habits reduce digestion and absorption of nutrients and lead to micronutrient deficiency and malnutrition[52-57]. In summary, the results indicate that the HHAS-HSS presents good reliability and validity among high school students in Anhui Province, China, and is a new and effective tool for assessing the risk of hidden hunger.…”
Section: Discussionmentioning
confidence: 99%